THE EFFECT OF PACLOBUTRAZOL CONCENTRATION AND NPK FERTILIZER DOSAGE ON THE PRODUCTION OF LONG BEANS (VIGNA SINENSIS L) BASED ON QUANTITY AND QUALITY - Fitriana, Vira Divka; Widiwurjani, Widiwurjani; Sulistyono, Agus (International Journal of Multidisciplinary Research and Literature, 2024)
The production of long bean plants is still relatively low compared to other countries. Factors that can cause low production of long bean plants and decrease yearly include limited knowledge of farmer cultivation techniques, using local varieties with low yield potential, and inappropriate or unbalanced fertilization so that long bean plants have low productivity. This research was conducted from December 2023 - to February 2024 at Dander Village Land, Dander District, Bojonegoro Regency, East Java. This experiment was arranged using RPT (Divided Plots Design) with two treatment factors, namely the frequency of NPK fertilizer application as a subplot and paclobutrazol as the main plot so that there are two factors. The first factor is paclobutrazol concentration (P), which includes four treatment levels: 0 ppm (P0), 125 ppm (P1), 150 ppm (P2), and 175 ppm (P3). Meanwhile, the second factor is the dose of NPK fertilizer (N), which consists of 4 treatment levels: 300 kg/ha (N1), 350 kg/ha (N2), 400 kg/ha (N3), and 450 kg/ha (N4). The combined treatment of paclobutazol concentration of 175 ppm and NPK fertilizer dose of 18 g/plant gave the best results in the parameters of pod length (76,00 cm), pod weight (41,93 g) and number of seeds (18,00 seeds). The treatment of paclobutrazol concentration of 150 ppm gave the best results in the parameters of the number of pods per plant from week 2 to week 4 (557,57 g, 340,00 g and 312,26 g), the total number of pods per plant (68,83), weight of pods per plant week 2 and 3 (557, 57 g and 340,00 g), total pod weight per plant (1766,39 g), pod weight per plot week two and week 5 (4,29 kg and 2,03 kg), total pod weight per plot (11,53 kg), pod weight per hectare (44,16) and fruit set (80,01%). The treatment of NPK fertilizer dose of 18 g/plant gave the best results in weight per pod (41,93 g) and pod weight per plot in week 1 (1,45 kg).